Assessing the Value of Library Resources for Renewal Negotiations - Becker, Louis Thacher; Gould, Elyssa M; Mezick, Jennifer A (Qualitative and Quantitative Methods in Libraries; Vol 10 No 3 (2021): September issue 2021, 2021)
This paper details a number of methods used by staff at the University of Tennessee, Knoxville Libraries throughout 2019 to assess the value of library resources and inform renewal negotiations for electronic resources. This paper discusses quantitative data from usage reports, access issue reports, citation analysis; input gathered from subject librarians; default annual cost increase caps; data analysis using PowerBI; and collaborative decision-making committees. Combining these evaluative methods provided a multi-faceted approach to the data to make evidence-based decisions on resource value.